JURIDICAL ANALYSIS OF THE REGULATIONS OF THE NATIONAL COLLECTIVE MANAGEMENT INSTITUTE (LMKN) IN TERMS OF COPYRIGHT INSTITUTIONS IN INDONESIA - Moch Rizky Giri; Hardian Iskandar; Dodi Jaya Wardana (Jurnal Justiciabelen, 2022)
Songs and/or music are copyright protected works. As the holder of Copyright and Related Rights, works belonging to the author that are used for commercial purposes have the right to obtain exclusive rights arising from declarative principles after the work of the author is heard. The emergence of Government Regulation No. 56 of 2021 concerning Management of Copyright Royalties for Songs and/or Music which has come into force since March 2021 as a rule to be able to optimize the function of managing copyright royalties from the use of works and related rights products, especially in songs or music. This thesis analyzes the urgency of the establishment of the National Collective Management Institute, the Legal Basis of the National Collective Management Institute, the powers and duties of the Collective Management Institute (LMK) and the National Collective Management Institute (LMKN) in managing music royalties used for commercial and protection purposes. Laws carried out by the National Collective Management Institute and based on Intellectual Property (IP). This thesis was written using a normative legal research method, which is an approach method through legislation whose norms are used as the main source in this research In addition, in this thesis research the author also uses an approach with the concept of understanding the principles regarding copyright as the exclusive right of the creator. From the research results, it has been concluded that there are two institutions that have different duties and authorities, the urgency of the importance of establishing a National Collective Management Institute for the management of Song and/or Music Copyright royalties, the legal basis of the National Collective Management Institute and the legal protection provided by LMKN on the management of royalties for Song and/or Music Copyrights in Indonesia.